The Reception of Víga-Glúms saga in Seventeenth-century Icelandic Manuscripts - Müller, Ermenegilda, 1992- (2016)
Víga-Glúms saga is a short example of the Íslendingasögur genre, whose plot is set in tenth-century Eyjafjörður. This thesis addresses the transmission and reception of the text in seventeenth-century Iceland through the codicological analysis of ten manuscripts, which have been selected according to their date of production, their textual integrity, and their accessibility in Icelandic collections. Their material characteristics are analyzed using a combination of descriptive and quantitative methods. The observations made here concern the manuscripts’ contents, their textual density and layout, the type and level of decoration, and extra-textual elements (such as marginalia) found in them. The commissioners, scribes and owners of these manuscripts are also identified, and the relationships between them are investigated. The approach aims to consider how and by whom Víga-Glúms saga was copied and read in a time-period that has been noted for its importance in the transmission of medieval Icelandic literature.